NASAKH DALAM HUKUM ISLAM - Mayangsari R., Galuh Nashrullah Kartika (An-Nisbah: Jurnal Ekonomi Syariah, 2016)
In Ulumul Qurâan, the existence of discourse about abrogating (Nasakh) is the real proof that there is a dialectic relationship between revelation andreality. Nasakh is the cancellation of the law. It could be eliminating and releasing the text of the law referring to reading. It also could be defending the text to show the instruction of abrogated law. The research is based on qualitative descriptive study that limits the study on the Mawaris and Wasiyat verses. The paper is expected to provide scientific contributions in the formof conceptualization of Ulumul Qurâan oriented to legal legislation and to provide intellectual contributions that combine theory of Nasakh in Ulumul Qurâan through a legal context of usul fiqh. Therefore, it is also possible tobe an alternative development of Philosophy of Islamic Law.Keywords: Nasakh, Legal Legislation, Wasiat, Mawaris.